Minimum-income benefits in OECD countries: policy design, effectiveness and challenges - Herwig Immervoll (Institute for the Study of Labor (IZA), 2009)
Almost all OECD countries operate comprehensive minimum-income programmes for working-age individuals, either as last-resort safety nets alongside primary income replacement benefits, or as the principal instrument for delivering social protection. Such safety-net benefits aim primarily at providing an acceptable standard of living for families unable to earn sufficient incomes from other sources. This paper provides an overview of social assistance and other minimum-income programmes in OECD countries, summarises their main features, and highlights a number of current policy challenges.
Keywords: I38; H53; D31; H31; 330; Social assistance; negative income tax; welfare to work; poverty; Soziale Mindestsicherung; Sozialhilfe; Negative Einkommensteuer; Aktivierende Sozialhilfe; Sozialpolitik; Vergleich; OECD-Staaten